2014
DOI: 10.1080/15321819.2014.920714
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and High Negativity of IgG Antibodies Against Human Papillomavirus (HPV) Type 6, 11, 16, and 18 Virus-like Particles in Women of Childbearing Age in Port Harcourt, Nigeria

Abstract: This study reports the seroepidemiology and high negativity of IgG antibodies against the most common low-and high-risk HPVs among sexually active women of childbearing age in Port Harcourt, Nigeria. A total of 182 consented women (age range 19-45 years) were consecutively recruited to participate in the study. Using a Performa specifically designed for this study, pertinent socio-demographic/behavioral data were collected. Five 5 mL blood samples were also collected (aseptically) from each woman. Plasma of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Low seroprevalence of 6.6% among 91 female subjects aged 16-40 years was detected using the Dia.Pro ELISA kit in a study performed by Adekunle et al(11). In Nigerian study using the same kit, Okonko et al(17) revealed high anti-HPV seronegativity of 95.1% among 182 women of childbearing age (age range 19-45 years), while Faneye et al(18) determined a slightly higher percentage antibody response in about 28.6% and 30% of unvaccinated men and women, respectively, attending the STI clinics. Also, using VLP-based ELISA kit Lu et al(19) reported the presence of anti-HPV IgG antibodies to HPV16/18 in 13.3% and 19.8% of males aged 18-25 and 26-35 years, respectively.…”
mentioning
confidence: 98%
“…Low seroprevalence of 6.6% among 91 female subjects aged 16-40 years was detected using the Dia.Pro ELISA kit in a study performed by Adekunle et al(11). In Nigerian study using the same kit, Okonko et al(17) revealed high anti-HPV seronegativity of 95.1% among 182 women of childbearing age (age range 19-45 years), while Faneye et al(18) determined a slightly higher percentage antibody response in about 28.6% and 30% of unvaccinated men and women, respectively, attending the STI clinics. Also, using VLP-based ELISA kit Lu et al(19) reported the presence of anti-HPV IgG antibodies to HPV16/18 in 13.3% and 19.8% of males aged 18-25 and 26-35 years, respectively.…”
mentioning
confidence: 98%